2011
DOI: 10.3892/ijmm.2011.600
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of Celastrol on hypoxia-mediated angiogenesis and metastasis via the HIF-1α pathway

Abstract: Abstract. celastrol, a natural biologically active compound isolated from Tripterygium wilfordii Hook F root extracts, has been shown to possess antitumor properties and therefore, is an interesting candidate for the development of novel chemotherapeutic cancer agents. In this study, we have demonstrated that celastrol is a potent inhibitor of hypoxia-induced angiogenic and metastatic activity as shown by a decrease in the proliferation of both endothelial and cancer cells, blocking of migration as well as of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…A previous study showed that treating HepG2 cells with Celastrol for 16 h decreased the HIF-1α mRNA level under normoxia and hypoxia and inhibited hypoxia-induced accumulation of the HIF-1α protein in the nuclei of HepG2 cells [15]; however, in our study, exposure of HepG2 cells for a shorter amount of time yielded the opposite result. In our system, treating cells with Celastrol for 6 h did not influence HIF-1α transcription, as its mRNA level did not change after Celastrol treatment under normoxia or hypoxia.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…A previous study showed that treating HepG2 cells with Celastrol for 16 h decreased the HIF-1α mRNA level under normoxia and hypoxia and inhibited hypoxia-induced accumulation of the HIF-1α protein in the nuclei of HepG2 cells [15]; however, in our study, exposure of HepG2 cells for a shorter amount of time yielded the opposite result. In our system, treating cells with Celastrol for 6 h did not influence HIF-1α transcription, as its mRNA level did not change after Celastrol treatment under normoxia or hypoxia.…”
Section: Discussioncontrasting
confidence: 93%
“…In addition to treating autoimmune and neurodegenerative diseases by its anti-oxidative and anti-inflammatory effects [4], [5], Celastrol is frequently investigated for its potential anti-cancer activities in vitro and in vivo , including inhibiting tumor cell proliferation, inducing apoptosis in different types of cancer cells [6][9] and synergistically enhancing the cytotoxicity of radiotherapy and some chemotherapeutic agents [10][13]. Although previous studies have reported that Celastrol has the potential to inhibit HIF-1α mRNA transcription and suppress hypoxia-induced angiogenesis and tumor metastasis [14], [15], in this study, we found that a short amount of time exposure of Celastrol did not affect the HIF-1α mRNA levels. Instead, we found that Celastrol could induce HIF-1α protein accumulation in multiple cancer cell lines in an oxygen-independent manner and that the enhanced HIF-1α protein entered the nucleus and promoted the transcription of the HIF-1 target genes VEGF and Glut-1.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of celastrol on angiogenesis is mediated by the suppression of HIF-1α, through HSP90 (122) and mTOR/p70S6K/eIF4E pathway inhibition and ERK1/2 phosphorylation (123, 124). This inhibition of HIF-1α leads to the decrease of its target genes, such as the VEGF , that are crucial in the angiogenic process.…”
Section: Anticancer Properties Of Celastrolmentioning
confidence: 99%
“…HIF-1β is considered to be an aryl hydrocarbon nuclear translocator (ARNT), whereas HIF-1α has been recognized as an oxygen-regulated subunit that mediates the function of HIF-1 (3). A series of studies have previously shown that the overexpression of HIF-1α was involved in the pathogenesis of tumor angiogenesis (4,5), invasion (6,7), metastasis (68) and resistance to chemotherapy (9,10). Several studies have focused on whether HIF-1α expression in human laryngeal carcinoma tissue is associated with tumor progression and lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%